2012
DOI: 10.1159/000336518
|View full text |Cite
|
Sign up to set email alerts
|

Renal Adaptation to Gentamicin-Induced Mineral Loss

Abstract: Background: Gentamicin, a well-known nephrotoxic drug, affects calcium and magnesium homeostasis. Although gentamicin induces urinary calcium and magnesium wasting immediately, it rarely causes significant hypocalcemia or hypomagnesemia clinically. Methods: We conducted an animal study to investigate the renal adaptation in calcium and magnesium handling after gentamicin treatment and effects on the expression of calcium and magnesium transport molecules in distal tubule. Gentamicin (40 mg/kg) was injected dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
1
8
4
Order By: Relevance
“…To compensate for the large loss of Ca, active Ca transporters such as TRPV5 and TRPV6 in the downstream DCT are upregulated (15). A similar compensatory mechanism has been reported in the gentamicin-and diabetes-induced hypercalciuria by our group (14,16). Thiazides induce hypocalciuria via different mechanisms depending on the volume status: with volume depletion, increased passive reabsorption in PT is the key mechanism (18); without volume depletion, the increased Ca reabsorption mainly occurs in the DCT via upregulation of TRPV5/6 and CBD-28k (13).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…To compensate for the large loss of Ca, active Ca transporters such as TRPV5 and TRPV6 in the downstream DCT are upregulated (15). A similar compensatory mechanism has been reported in the gentamicin-and diabetes-induced hypercalciuria by our group (14,16). Thiazides induce hypocalciuria via different mechanisms depending on the volume status: with volume depletion, increased passive reabsorption in PT is the key mechanism (18); without volume depletion, the increased Ca reabsorption mainly occurs in the DCT via upregulation of TRPV5/6 and CBD-28k (13).…”
supporting
confidence: 55%
“…A genetic defect in claudin-16 causes hypomagnesemia with hypercalciuria and nephrocalcinosis (9). The expression of claudin-16 is not affected by salt or fluid intake (17), or Mg-wasting drugs such as gentamicin (16) and cisplatin (11). Since CTZ acts on the DCT, it is unlikely to affect the expression of claudin-16, which locates to the TALH.…”
mentioning
confidence: 99%
“…1,2 Some studies in newborns and animals have shown that gentamicin increases urinary calcium excretion. [11][12][13][14][15] Injection every 36-48 hours is a new recommendation for intravenous gentamicin treatment in newborns. 3 Following this new recommendation, there have been no further studies on the effects of extended gentamicin dosage on urinary calcium excretion in newborns.…”
Section: G Entamicin Is a Common First-line Antibiotic Therapy For Inmentioning
confidence: 99%
“…Among the other group of medications often used in children with malignancy, it is believed that calcineurin inhibitors, cyclosporine and tacrolimus, often used in transplanted patients are causing hypomagnesemia by decreasing both sodium reabsorption and TRPM-6 expression in the distal tubule thus causing renal magnesium wasting [23,24,61]. As depicted in Figure 2, gentamicin and other aminoglycosides exert their magnesuric effect by stimulating the calcium sensor receptor located at the basolateral side of the thick ascending limb of the loop of Henle [35,62]. Physiologically the activation of the receptor by hypercalcemia and hypermagnesemia causes decreased sodium reabsorption and consequently that of magnesium.…”
Section: Renal Causesmentioning
confidence: 99%